FAKTOR RISIKO DERMATITIS TANGAN PADA PEKERJA TRADISIOAL INDUSTRI GERABAH (SEBUAH STUDI OBSERVASIONAL) - Ratih Pramuningtyas; Delima Anggraini Hudini (Universitas Muhamadiyah Surakarta, 2019)
Hand dermatitis (HD) is a form of occupational dermatitis that frequently occurs. It is caused by exposure to chemicals and the environment. Hand dermatitis is often related to work and pottery industry was one of them. Clay as the main ingredient in the traditional pottery industry contains ingredients that potentially irritant and allergenic. The frequency and risk factors that affected the frequency of HD in pottery industry worker was unknown. Objective of this study was to determine frequency and history of atopic, wet work, and contact duration as risk factors that affected that frequency of HD in traditional pottery industry worker. Analytic observational study with a cross-sectional design. Sixty subjects were included in this study, 53,3% are men. The mean age of subjects was 43.75 years old. Frequency of HD on pottery industral worker was 58,33%. In bivariate analysis, history of atopy, wet work, and contact duration were significantly associated with the incidence of hand dermatitis. Hand dermatitis that appears on the subject is probably caused by calcium oxide, aluminum oxide, and chromium which was the content of clay as the industry's main raw material. Conclusion of this study was frequency of hand dermatitis 58.33% and there was a significant association between a history of atopy, wet work, and contact duration with hand dermatitis among traditional pottery industry workersKey word : Hand Dermatitis, Risk Factor, History Of Atopic, Wet Work, Contact Duration, Pottery